The Effects of Short-Term and Long-Term Testosterone Supplementation on Blood Viscosity and Erythrocyte Deformability in Healthy Adult Mice - Guo, Wen (Endocrinology, 2015)
Testosterone treatment induces erythrocytosis that could potentially affect blood viscosity and cardiovascular risk. We thus investigated the effects of testosterone administration on blood viscosity and erythrocyte deformability using mouse models. Blood viscosity, erythrocyte deformability, and hematocrits were measured in normal male and female mice, as well as in females and castrated males after short-term (2 wk) and long-term (5–7 mo) testosterone intervention (50 mg/kg, weekly). Castrated males for long-term intervention were studied in parallel with the normal males to assess the effect of long-term testosterone deprivation. An additional short-term intervention study was conducted in females with a lower testosterone dose (5 mg/kg). Our results indicate no rheological difference among normal males, females, and castrated males at steady-state. Short-term high-dose testosterone increased hematocrit and whole-blood viscosity in both females and castrated males. This effect diminished after long-term treatment, in association with increased erythrocyte deformability in the testosterone-treated mice, suggesting the presence of adaptive mechanism. Considering that cardiovascular events in human trials are seen early after intervention, rheological changes as potential mediator of vascular events warrant further investigation.